Generation of scFv-Monoclonal Antibody Avian Influenza Diagnostic tests - Simson Tarigan; . Sumarningsih (Indonesian Center for Animal Research and Development (ICARD), 2019)
The need for rapid diagnostic tools or point- of- care diagnostic tests for Avian Influenza in Indonesia is very high and the price of these imported diagnostic tools is very expensive. As a result, a large budget requires to provide the needs. The main component of a rapid diagnostic tool is the monoclonal antibody (mAb) specifically recognized influenza viruses. The objective of this study was to produce mAb that can recognize all subtypes of Avian Influenza viruses using the phage display technology. Influenza-A focused scFv commercial library was panned using alternating recombinant H1N1 NP and H5N1 virions. Whereas, bacteriophages bound to the panning baits were eluted with serum from H5N1-infected chickens. Phagemid from suppressor E. coli (TG1) infected with bacteriophage displaying anti-NP on its surface was isolated and then transformed into a non-suppressor E. coli (HB2151) to express NP-scFv. Monoclonal NP-scFv antibody with a molecular weight of about 27 kDa was purified from the culture supernatant using a nickel-chromatography column. The amount of pure NP-scFv obtained was around 1.2 mg /L culture. As an additional component for its use in immunoassays, antibody to NP-scFv was produced in rabbits. The generating polyclonal antibody recognized the NP-scFv specifically and sensitively. The anti-NP-scFv monoclonal antibody and the anti rabbit scFv polyclonal antibody produced in this study are envisaged appropriate for the development of diagnostic tools for point-of-care for Avian Influenza.